2014
DOI: 10.1111/apt.12881
|View full text |Cite
|
Sign up to set email alerts
|

The impact of type 2 diabetes and obesity on the long‐term outcomes of more than 85 000 liver transplant recipients in the US

Abstract: Summary Background Type 2 diabetes is known to negatively impact the outcome of chronic liver disease. Aim To evaluate the impact of diabetes on the outcomes of liver transplants (LT). Methods Study cohort included adults (>18 years) who received LT in the US between 1994 and 2013 (The Scientific Registry of Transplant Recipients). Pre‐ and post‐transplant diabetes was recorded in patients with mortality follow‐up. Results We included 85 194 liver transplant recipients. Of those, 11.2% had history of pre‐trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 34 publications
1
47
2
Order By: Relevance
“…To our knowledge, this is the first nationwide population-based study to investigate the effects of DM on the risk of post-LTx mortality and morbidity in an Asian population. Contrary to the previous publications [13][14][15][16], we observed that DM patients did not exhibit increased risks of early post-LTx morbidities or mortality compared with non-DM patients. However, further analysis showed that preexisting DM with renal manifestations was associated with a significantly higher mortality rate within 90 days after LTx, in comparison with the non-DM cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first nationwide population-based study to investigate the effects of DM on the risk of post-LTx mortality and morbidity in an Asian population. Contrary to the previous publications [13][14][15][16], we observed that DM patients did not exhibit increased risks of early post-LTx morbidities or mortality compared with non-DM patients. However, further analysis showed that preexisting DM with renal manifestations was associated with a significantly higher mortality rate within 90 days after LTx, in comparison with the non-DM cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, some studies have evaluated the risk of perioperative mortality and complications after LTx in DM patients in a population-based setting [13][14][15][16]. However, there has been no similar study in an Asian population.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have examined the association between pre‐transplant diabetes and obesity on post‐transplant outcomes . These studies have examined the independent effects of obesity and diabetes; however, given the frequency with which they co‐exist, it is surprising that there is a lack of knowledge regarding the additive effects of concomitant metabolic factors on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference in cardiovascular mortality was found among patients with diabetes and obesity compared with those without. This may be due to lack of power to determine an association, noting that larger studies have found diabetes to be a risk factor for cardiovascular death . Significantly, the proportion of deaths due to cardiovascular disease in our entire cohort was only 3.6%, which is lower than reported in the SRTR (10% at 5 years) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation